The Relationship Between Authentic Leadership, Psychological Empowerment, Role Clarity, and Work Engagement: Evidence From South Africa - Towsen, Tasmin; Stander, Marius Wilhelm; van der Vaart, Leoni (Frontiers in Psychology, 2020)
Employees in the mining sector are faced with a demanding work environment due to external challenges impacting on the organisation. Optimising their engagement is vital in weathering a demanding environment. The aim of this study was to (a) position authentic leadership and psychological empowerment as enablers of work engagement; (b) to investigate the processes (i.e. psychological empowerment) through which authentic leadership exerts its effect on work engagement, and (c) to determine whether contextual factors (i.e. role clarity) influenced this process. A cross-sectional research design was employed to collect data from 236 employees employed by a coal-mining organisation within South Africa. The Authentic Leadership Inventory, Psychological Empowerment Questionnaire, Measures of Role Conflict and Ambiguity Questionnaire, and UWES-9 was administered to collect data. A moderated-mediation investigation was employed to test the hypotheses. Results supported the value of authentic leadership to enhance work engagement, both directly and indirectly via psychological empowerment. Results also concluded that authentic leadership exerts its influence on work engagement through psychological empowerment, regardless of employees’ levels of role clarity. Authentic leadership literature is limited, not only in the South African context but also in the mining sector. The study not only extends authentic leadership literature by investigating its outcomes in a South African mining organization, but it also does so by investigating the boundary conditions under which authentic leadership exerts its influence. The boundaries (i.e. moderation) within which leadership-subordinate relationships (i.e. mediation) function are often neglected in favor of simplified investigations of mediation processes only.